Chromatographic NMR Spectroscopy with Hollow Silica Spheres. Issue 8 (25th January 2016) - González‐García, Tania; Margola, Tommaso; Silvagni, Adriano; Mancin, Fabrizio; Rastrelli, Federico
Abstract: The use of micrometric hollow silica spheres is described as a strategy to reduce magnetic field inhomogeneities in the context of NMR chromatography. When employed as a stationary phase, hollow silica microspheres allow the use of common solution‐state NMR instruments to measure the diffusion coefficient perturbation induced by the interaction of the analytes with the silica surface. Abstract : A (w)hole lot better : Hollow silica microspheres made possible the use of solution‐state NMR instruments to analyze mixtures of small molecules by chromatographic NMR spectroscopy (see picture). The silica microspheres clearly provide major advantages over conventional stationary phases.